2021
DOI: 10.3390/microorganisms9081725
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Sex on Antibody Response Following the Second Dose of COVID-19 BNT162b2 mRNA Vaccine in Greek Healthcare Workers

Abstract: Anti-SARS-CoV-2 spike RBD (receptor-binding domain) IgG antibody levels were monitored in 1643 volunteer healthcare workers of Eginition, Evangelismos, and Konstantopoulio General Hospitals (Athens, Greece), who underwent vaccination with two doses of COVID-19 BNT162b2 mRNA vaccine (Pfizer) and had no history of SARS-CoV-2 infection. Venous blood was collected 20–30 days after the second vaccine dose and anti-RBD IgG levels were determined using CMIA SARS-CoV-2 IgG II Quant (Abbott) on ARCHITECT i System or AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
30
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 30 publications
(47 reference statements)
12
30
4
2
Order By: Relevance
“…In agreement with previous reports, our study supports a role for age in the development and amount of antibody response. Moreover, this significant relation between lower serological values and increasing age is observed also at different time lapses from vaccination, including the first weeks [ 5 , 6 , 12 , 13 , 14 , 15 , 16 ], up to 3–6 months such as in our and other studies [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with previous reports, our study supports a role for age in the development and amount of antibody response. Moreover, this significant relation between lower serological values and increasing age is observed also at different time lapses from vaccination, including the first weeks [ 5 , 6 , 12 , 13 , 14 , 15 , 16 ], up to 3–6 months such as in our and other studies [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…Another demographic feature that we found associated with lower serological levels is male gender (adjusted for all other variables), a finding that deserves further investigations. Several studies evidenced a lower antibody response to BNT162b2 vaccine in men than in women [ 6 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 19 ]. Some studies suggested that this difference could be influenced by the serological assay used for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected finding was the average anti-S1 Ab titer >40.000 AU/mL after the second dose in the LTR group with autoimmune primary liver diseases (primary sclerosing cholangitis or autoimmune hepatitis), which confirmed previous observations that autoimmunity itself does not hamper vaccination responses [28]. It is unclear whether the Abs are the crucial and only indicator of immunity or whether their absence leads to a complete lack of response to vaccination.…”
Section: Discussionsupporting
confidence: 80%
“…Also, age-related result could be explained by immunosenescence which is a series of age-related changes in immune system with changes of the cells of the immune system, the soluble molecules that guide the maintenance and function of the immune system, and the lymphoid organs that coordinate both the maintenance of lymphocytes and the initiation of immune responses [ 29 ]. Although efficacy was not verified in this study, Vassilaki et al reported higher antibody titers in females and younger vaccinated recipients [ 30 ]. In addition, a systematic review reported potential sex-related differences in efficacy and safety [ 31 ].…”
Section: Discussioncontrasting
confidence: 56%